2003
DOI: 10.3928/0098-9134-20030701-07
|View full text |Cite
|
Sign up to set email alerts
|

Reminiscence Therapy for Older Women with Depression: Effects of Nursing Intervention Classification in Assisted-Living Long-Term Care

Abstract: The purpose of this study was to determine the effects of a 3-week, six-session Nursing Interventions Classification (NIC) reminiscence intervention on the level of depression among elderly women residing in one assisted-living long-term care facility using a pre-test--post-test, quasi-experimental design. A convenience sample of 30 women (M = 81.7 years) participated in the study. Participants were randomly assigned to one of two groups, an experimental group that received the NIC reminiscence intervention an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
2
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 33 publications
2
48
2
4
Order By: Relevance
“…This finding was consistent with the results in several previous studies (Ashida, 2000;Haight et al, 2000;Jones, 2003;Wang, 2005Wang, , 2007Beth, 2006). During reminiscence therapy, at first the participants passively shared their life experiences with others.…”
Section: Changing Of the Depressed Moodsupporting
confidence: 83%
See 2 more Smart Citations
“…This finding was consistent with the results in several previous studies (Ashida, 2000;Haight et al, 2000;Jones, 2003;Wang, 2005Wang, , 2007Beth, 2006). During reminiscence therapy, at first the participants passively shared their life experiences with others.…”
Section: Changing Of the Depressed Moodsupporting
confidence: 83%
“…The evaluation of reminiscence therapy was done using the following tools: Geriatric Depression Scale short form (GDS-SF); Cornell Scale for Depression in Dementia (CSDD), and Hamilton Rating Scale of Depression (HRSD). Results from previous studies have shown that reminiscence therapy improves depressive symptoms, with the average GDS-SF score falling from 13.7-6.36 points to 12.3-4.29 points, and the average CSDD score decreasing from 7.37 to 6.23 points (Ashida, 2000;Jones, 2003;Wang, 2005Wang, , 2007Beth, 2006). The positive effects persisted when measured at 1 and 3 years post-therapy ( p < .05) (Haight et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Azzolin K, et al gave the same taxonomy involved in patients with heart failure and proved the effectiveness of the multiple (NIC) nursing intervention [32]. The complete compliance of these activities may work effectively in refining the lifestyle and also improve the quality of life especially in cardiac patients [33]. This study enhances to the local, national and global awareness base about the effectiveness of nursing intervention for depression reduction.…”
Section: Discussionmentioning
confidence: 64%
“…Gruplar yaş, medeni durum, fiziksel ve ruhsal kapasite ve yaşlıların birbirleriyle anlaşma durumu göz önüne alınarak oluşturulmalıdır. [51,52] Yaşlılar bu özelliklerine göre kendini güvende hissedebilecekleri ve rahat ifade edebilecekleri gruplara ayrılmalıdır.…”
Section: Anımsama Terapisi Uygulamasıunclassified